2013
DOI: 10.1371/journal.pone.0061051
|View full text |Cite
|
Sign up to set email alerts
|

Major Effect of Hydrogen Peroxide on Bacterioplankton Metabolism in the Northeast Atlantic

Abstract: Reactive oxygen species such as hydrogen peroxide have the potential to alter metabolic rates of marine prokaryotes, ultimately impacting the cycling and bioavailability of nutrients and carbon. We studied the influence of H2O2 on prokaryotic heterotrophic production (PHP) and extracellular enzymatic activities (i.e., β-glucosidase [BGase], leucine aminopeptidase [LAPase] and alkaline phosphatase [APase]) in the subtropical Atlantic. With increasing concentrations of H2O2 in the range of 100–1000 nM, LAPase, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 56 publications
(72 reference statements)
0
22
0
1
Order By: Relevance
“…In this setting, these AOA perform nitrification (32,33), often under oligotrophic conditions (ammonia concentrations <5 nM) (21). In these environments, the H 2 O 2 concentration is also extremely low (i.e., in the 5-10-nM range) (34). Therefore, over evolutionary time, many autotrophic AOA may have dispensed with their burden of ROS-detoxification genes (such as those encoding catalase) to streamline their genome for efficient use of rare resources.…”
Section: Peroxidase Activity By Bacteria Explains the High Rate Of Ammentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting, these AOA perform nitrification (32,33), often under oligotrophic conditions (ammonia concentrations <5 nM) (21). In these environments, the H 2 O 2 concentration is also extremely low (i.e., in the 5-10-nM range) (34). Therefore, over evolutionary time, many autotrophic AOA may have dispensed with their burden of ROS-detoxification genes (such as those encoding catalase) to streamline their genome for efficient use of rare resources.…”
Section: Peroxidase Activity By Bacteria Explains the High Rate Of Ammentioning
confidence: 99%
“…There may be H 2 O 2 -tolerant AOA ecotypes featuring traits adapted to distinct habitats. For example, in the epipelagic zone, photochemical reactions can boost H 2 O 2 concentrations by orders of magnitude (i.e., up to ∼0.4 μM) (20,34). Furthermore, single-cell genome analysis of epipelagic AOA ecotypes has revealed that they do harbor putative catalase genes (35).…”
Section: Peroxidase Activity By Bacteria Explains the High Rate Of Ammentioning
confidence: 99%
“…Factors resulting in a negative or mixed effect include photochemical production of inhibitory substances such as hydrogen peroxide (Angel et al, 1999;Baltar et al, 2013;Farjalla et al, 2001;Gjessing and Källqvist, 1991;Kaiser and Sulzberger, 2004;Leunert et al, 2014;Lund and Hongve, 1994;Morris et al, 2011;Scully et al, 2003a;Tranvik and Kokalj, 1998;Weinbauer and Suttle, 1999), release of toxic metals (e.g., Pb, Cu, Ni, Cd, and Hg) from DOM complexes (Haverstock et al, 2012;Tonietto et al, 2011;Winch and Lean, 2005), photolysis of DOM to form substances that are both biologically and photochemically refractory (Kieber, 2000;Stubbins et al, 2010), deactivation of enzymes (Scully et al, 2003b;Vähätalo et al, 2003), changes in the BGE (Abboudi et al, 2008;McCallister et al, 2005;Mopper and Kieber, 2002;Pullin et al, 2004;Smith and Benner, 2005), changes in microbial populations (i.e., community structure) in response to photoproduced substrates or toxic substances (Abboudi et al, 2008;Calza et al, 2008;Lønborg et al, 2013;Piccini et al, 2009), and prior photochemical history, i.e., photon dose-related bleaching (Reader and Miller, 2014). In addition to the above factors, a negative or mixed effect on biological activity can result from reactions of biologically produced ROS, e.g., H 2 O 2 (Palenik and Morel, 1990;Diaz et al, 2013) with photochemically produced reduced metals, e.g., Fe(II), Mn(II), and Cu(I) (Barbeau, 2006;Brinkmann et al, 2003;…”
Section: Coupled Photochemical-microbial Doc Degradation: Impact On Mmentioning
confidence: 99%
“…In contrast, studies with long-term incubation times (e.g., days to weeks or longer) often showed an initial lag period (with no or negative effect) followed by a positive effect on microbial activity (Anesio et al, 2005;Biddanda and Cotner, 2003;Judd et al, 2007;McCallister et al, 2005;Obernosterer and Benner, 2004;Pullin et al, 2004;Smith and Benner, 2005) or enzymatic activity (Vähätalo et al, 2003). The initial lag (or negative effect) may have been due to the photoproduction of inhibitory substances such as ROS or toxins (Anesio et al, 1999(Anesio et al, , 2005Angel et al, 1999;Baltar et al, 2013;Calza et al, 2008;Diamond, 2003;Farjalla et al, 2001;Goldstone et al, 2002;Kaiser and Sulzberger, 2004;Leunert et al, 2014;Lund and Hongve, 1994;Morris et al, 2011;Scully et al, 2003b;Tranvik and Kokalj, 1998;Weinbauer and Suttle, 1999) that decayed over time (Anesio et al, 2005;Goldstone et al, 2002), or induced a change in the microbial community structure to species less affected by photoproduced toxins and/or better adapted to utilizing photoproduced products (Abboudi et al, 2008;Judd et al, 2007;Langenheder et al, 2006;Pérez and Sommaruga, 2007;Piccini et al, 2009;Pullin et al, 2004;Vähätalo et al, 2003). Alternatively, the lag period may be the time needed for microbes to biodegrade photoaltered high molecular weight (HMW) DOM to LMW membrane-transp...…”
Section: Coupled Photochemical-microbial Doc Degradation: Impact On Mmentioning
confidence: 99%
“…[4] At a first glance the intracellular levels of H 2 O 2 and its dynamics in seawater have little in common. Yet, since H 2 O 2 is membrane permeable, its presence in seawater can cause deleterious effects to marine organisms such as bacteria and phytoplankton [Baltar et al, 2013;Morris et al, 2011]. On the other hand, marine microbes can influence H 2 O 2 dynamics in seawater by producing and degrading H 2 O 2 [Hansard et al, 2010;Palenik and Morel, 1988;Rose et al, 2010;Wong et al, 2003].…”
Section: Introductionmentioning
confidence: 99%